Performance of FPT, FTIR and DSC methods in cure monitoring of epoxy resins. (5th January 2022) - Sawicz-Kryniger, Katarzyna; Niezgoda, Paweł; Stalmach, Paweł; Starzak, Katarzyna; Wysocka, Alicja; Świergosz, Tomasz; Popielarz, Roman
Graphical abstract: Highlights: Performance of FPT, FTIR and DSC in cure monitoring of epoxy resins is compared. FPT parameters are linearly proportional to absolute epoxy groups conversions. A method for determination of activation energy directly from FPT data is described. Abstract: Addition polymerization of Epidian 5 and Rutapox 0162 epoxy resins with triethylenetetramine (TETA) or hexahydrophthalic anhydride (HHPA) was studied by F luorescence P robe T echnique (FPT), F ourier-T ransform I nfraR ed spectroscopy (FTIR) and D ifferential S canning C alorimetry (DSC) methods. The performance of those methods in real-time monitoring the reactions kinetics was evaluated. The relative reaction progress parameters provided by FPT were correlated with absolute epoxy groups conversions measured by FTIR and DSC. It has been found that the relationships are linear over a broad range of conversions. Moreover, a method for determination of activation energy of the reactions studied directly from FPT data without the need for calibration of the FPT parameters to absolute conversions has been described. The activation energies of the reactions studied, determined by FPT, turned out to be the same (i.e., within an experimental error) as those determined by DSC and those reported in literature, that makes the FPT a good alternative to FTIR and DSC methods for kinetic studies of chemical reactions.